2005
DOI: 10.1242/jeb.01431
|View full text |Cite
|
Sign up to set email alerts
|

Associative learning of plant odorants activating the same or different receptor neurones in the moth Heliothis virescens

Abstract: The importance of olfactory learning in host plant selection is well demonstrated in insects, including the heliothine moths. In the present study olfactory conditioning of the proboscis extension response was performed to determine the moths' ability to learn and discriminate three plant odorants: β-ocimene and β-myrcene (activating the same receptor neurone type), and racemic linalool (activating two different types). The conditioned stimulus (CS) was an air puff with each odorant blown into a constant air s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 39 publications
3
32
1
Order By: Relevance
“…While there is evidence in vertebrates of how this reduction in the error signal may be implemented biologically, such evidence is still lacking in invertebrates. Conditioning using the PER has been so successful that it has been established in other insects such as moths and flies (Medioni and Vaysse, 1975;DeJianne et al, 1985;Holliday and Hirsch, 1986;Brigui et al, 1990;Fan et al, 1997;Fresquet, 1999;Hartlieb et al, 1999;Daly and Smith, 2000;Fan and Hansson, 2001;Skiri et al, 2005) and for use with mechanosensory stimuli (Giurfa and Malun, 2004).…”
Section: Invertebrate Classical Conditioningmentioning
confidence: 99%
“…While there is evidence in vertebrates of how this reduction in the error signal may be implemented biologically, such evidence is still lacking in invertebrates. Conditioning using the PER has been so successful that it has been established in other insects such as moths and flies (Medioni and Vaysse, 1975;DeJianne et al, 1985;Holliday and Hirsch, 1986;Brigui et al, 1990;Fan et al, 1997;Fresquet, 1999;Hartlieb et al, 1999;Daly and Smith, 2000;Fan and Hansson, 2001;Skiri et al, 2005) and for use with mechanosensory stimuli (Giurfa and Malun, 2004).…”
Section: Invertebrate Classical Conditioningmentioning
confidence: 99%
“…The sucrose US (5·s) was applied with a toothpick 2.5·s after the onset of the odour puff, first to both antennae, and then to the extended proboscis. Because moths tend to be unresponsive at the beginning of conditioning because of low attention, the same method as in previous work was used to ensure learning success (Skiri et al, 2005): if the insect did not extend its proboscis at first encounter with the sucrose, the proboscis was forced out, and the insect was allowed to drink. This was not done in subsequent trials, meaning that the insects that failed to show PER were not rewarded.…”
Section: Experiments 1 Us Concentration Retention and Extinctionmentioning
confidence: 99%
“…antennae, mouthparts and tarsi, causes the hungry insect to extend its proboscis in order to feed. This response, the proboscis extension response (PER), has been utilised to study classical conditioning, particularly appetitive olfactory learning in several insect species, including the honeybee Apis mellifera (Bitterman et al, 1983;Menzel, 1993;Hammer and Menzel, 1995), the bumblebee Bombus terrestris (Laloi et al, 1999), and several moth species (Hartlieb, 1996;Fan et al, 1997;Daly et al, 2004;Skiri et al, 2005). In all these species, including moths, it was demonstrated that the olfactory conditioning of the PER is associative.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations